Swelling index, gel fraction, thermal and rheological properties of Centella asiatica hydrogel - Ahmed, Afnan Sh.; Bakhtiar, M. Taher; Mandal, Uttam Kumar; Md. Jaffri, Juliana (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2016)
The Hydrogels are three dimensional, water swollen structure composed of mainly hydrophilic homopolymers or copolymers like polyvinyl alcohol (PVA), Poly ethylene glycol (PEG) etc., utilized as a part of various biomedical fields, and are as yet producing for new encouraging applications. Hydrogel from PVA and PEG with Centella asiatica methanolic fraction was obtained by using freeze-thaw method. Gel fraction, swelling behavior, thermal and rheological properties were investigated. Five consecutive cycles of freezing and thawing formed an insoluble and entangled hydrogel. The developed hydrogel using the freezing–thawing method with PVA and PEG polymers and Centella asiatica methanolic extract was swellable, flexible and stable.